Vietnam Entrepreneurship Digital Transformation: a Lesson Learn from MSMEs in Hanoi and Ho Chi Minh City - Haque, Marissa Grace; Rimadias, Santi; Nelmida, Nelmida; Andriani, Meta; Putri, Vidiyanna Rizal; Sparta, Sparta; Zulfison, Zulfison; Haryanti, Enny (Doctoral Program of Social Science, Pasundan University, 2024)
Increasing people's welfare and leaps at all levels of national progress are important goals in developing MSMEs in Hanoi and Ho Chi Minh City, Vietnam. Through comprehensive training programs carried out by the country, Vietnam's MSMEs are developing rapidly. With an understanding of digital technology and effective-efficient business practices. In the operational realm, product and service quality, expanding market reach through online platforms. The adoption of digital technology and entrepreneurship training also opens up new opportunities for Vietnamese MSMEs to collaborate with other business actors, both at home and abroad, through G to G to B to B. Thus, MSMEs in the two cities in Vietnam become more competitive, and contribute to increasingly sustainable inclusive economic growth. This research tries to explore the relationship between the adoption of digital technology and entrepreneurship training with the financial literacy and business management abilities of MSMEs from Vietnam, as well as their impact on the welfare of the people in these two cities, for adoption by Indonesia.